Helmintofauna associada a répteis provenientes da Reserva Particular do Patrimônio Natural Foz do Rio Aguapeí, estado de São Paulo - Silva, Lidiane Aparecida Firmino da [UNESP] (2014)
The biomes Atlantic Forest and Savannah hold contact points known as “transition areas”. Such areas are highly complex because they harbor elements belonging to the two biomes and also distinct elements, which make them relevant due to the possibility of endemism. The aim of this study was to characterize the composition and structure of the helminth fauna associated with reptiles from a biome of transition area, located in the National Park “Foz do Aguapeí” (Reserva Particular do Patrimônio Natural – RPPN - Foz do Rio Aguapeí), Northwest portion of São Paulo State, Castilho municipality. It was necropsied 88 reptile specimens, comprised by five snake families (Boidae, Colubridae, Dipsadidae, Typhlopidae and Viperidae), five lizard families (Diploglossidae, Gymnophthalmidae, Mabuyidae, Teiidae and Tropiduridae), one crocodile family (Alligatoridae), and one chelonian family (Chelidae). A total parasite prevalence of 57% was observed. The helminthes recuperated represent 27 taxa: Acanthocephala (Cystacanth), Digenea (Cheloniodiplostomum testudinis, Infidum infidum, Infidum similis, Nematophila grandis, Telorchis birabeni, Travtrema stenocotyle and two unidentified morpho-types), Monogenea (Polystomoides brasiliensis and Polystomoides sp.), Cestoda (Crepidobothrium cf. gerrardii, Oochoristica sp. and Ophiotaenia sp.) and Nematoda (Brevimulticaecum sp., Brevimulticaecum pintoi, Cistos, Cosmocerca podicipinus, Hastospiculum digiticaudatum, Ortleppascaris alata, Parapharyngodon largitor, Physaloptera sp., Physalopteroides sp., Rhabdias sp., Serpinema monospiculatus, Spiroxys figuereidoi and Strongyloides ophidae). This study records 25 new hosts for different helminth species, and represents an important contribution for the knowledge of helminth fauna associated with reptiles from South America, broadening the parasitism records of hosts from the Neotropical region